"IOS11": A new, extended, interactive version of the "Inclusion of Other in the Self" scale - Malte Baader; Chris Starmer; Fabio Tufano; Simon Gächter (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
We introduce and test a new tool designed to measure "relationship closeness". Studying relationship closeness has a long history in psychology and is currently expanding in other fields including economics. Our new measurement tool is a refinement of the widely used "Inclusion of Other in the Self" scale (IOS for short) of Aron et al. (1992) and is designed to embody three key features. First, it retains attractive attributes of the standard IOS tool including being an effective measurement technique which is easy to implement and understand. Second, we enhance the scope for convenient use of the tool via the development of a portable interactive interface that will be particularly useful in online studies. Thirdly and crucially, through extensive pre-registered experimental testing, we demonstrate that our enhanced tool - IOS11 which features an 11-point response scale - outperforms previous versions of IOS in better proxying features of relationships captured by a range of more complex survey tools; the performance of IOS11 is also indistinguishable from that of the more complex "Oneness" measure of Cialdini et al. (1997) which uses the standard IOS as one of its two-item inputs.
Keywords: 330; Inclusion of other in the self scale; oneness; relationship closeness; psychometric evaluation; replication